Determination The Coefficient of Restitution in Object as Temperature Function in Partially Elastic Collision Using Phyphox Application on Smartphone - hamzarudin hikmatiar; Ishafit Ishafit; Mentari Eka Wahyuni (Science and Technology Indonesia, 2019)
This research aims to determine the coefficient of restitution in object experiencing partially elastic collision when the object falls free using the phyphox application on smartphone. In terms of experiment, this experiment was carried out five times with different temperature. The smartphone is connected on PC through the same wifi network or using tethering by entering the search address that available on phyphox application. After that, the smartphone placed on the board that used as a base when the object dropped, then the object released from the certain height. Data collecting process started by running the phyphox application through a PC to collect the measurement data. The data collected on smartphone is exported to Ms. Excel to fit the data and then the results are plotted in graphical form. The result of the analysis shows the coefficient of restitution value of the object that had variations based on experiment with each temperatures at 32 oC, 28 oC, 24 oC, 20 oC 18 oC and the coefficient of restitution values are 0.889 ± 0.006, 0.890 ± 0.008, 0.891 ± 0.003, 0.892 ± 0.003 and 0.893 ± 0.003. The result of research shows that the lower of the temperature so theres increasing on the coefficient of restitution. So that the coefficient of restitution has avarage’s value is 0.891±0.002. Keywords: coefficient of restitution ,smartphone, phyphox application